Developing metacognition in pre-primary childhood education in Nigeria and Uganda (2022)
Education is a process designed to develop skills and attitudes in learners, among these skills is metacognition. Societies have faulted educational institutions on its inability to produce graduates who can reason and decide rationally, this had prompted the search by scholars to resolve this challenge. This paper examined metacognition as a concept and how teachers can develop this skill in learners especially, those in the pre-school classes in Nigeria and Uganda. Metacognition is the ability to reflect on issues and personally take decisions that are rational and result in beneficial actions. The paper discussed various methods and theories of imparting this skill in early childhood learners which include the play-way, dramatisation and story-telling methods of teaching while the theories of learning considered include the Stimulus-Response and Cognitive theories. Models of learning like the Reggio Emilia and Friedrich Froebel's were enumerated as means by which the skill can be imparted. The paper concluded that the skill is indispensable if the process of education is to produce graduates competent in critical thinking and logical reasoning. It recommended that professionals should be employed to handle children's education, conducive environment be provided, while young learners should be encouraged to carry out independent actions with supervision from teachers.